2012
DOI: 10.4238/2012.august.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence analysis of mitochondrial DNA of aplastic anemia patients

et al.

Abstract: ABSTRACT. This study was primarily undertaken to test the hypothesis that mitochondrial DNA (mtDNA) mutations may be associated with aplastic anemia (AA). We analyzed mtDNA sequences from 15 patients with AA. The samples were obtained from bone marrow, and patients' oral epithelial cells were collected for normal tissue comparison. Total DNA was amplified by PCR after extraction, and these segments were then sent for sequencing. The results were compared with those of oral epithelial tissues as well as mtDNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Cells with an inadequate ATP supply may have difficulties in the properly segregation of chromo somes during mitosis. These factors may decrease energy metabolism, which can affect the self-renewal and differentiation of HSCs (Zhang and Sadek, 2014).The main site of energy metabolism is the mitochondria, and we recently found (Cui et al, 2012) that mutations of mtDNA may induce apoptosis through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cells with an inadequate ATP supply may have difficulties in the properly segregation of chromo somes during mitosis. These factors may decrease energy metabolism, which can affect the self-renewal and differentiation of HSCs (Zhang and Sadek, 2014).The main site of energy metabolism is the mitochondria, and we recently found (Cui et al, 2012) that mutations of mtDNA may induce apoptosis through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al . reported that mitochondrial DNA mutations were associated with aplastic anemia [39]. They found that mutation rates were particularly high in the ND2 coding region in the mitochondrial DNA genomes of patients with aplastic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the si�e of the PCR products presented in Table 2 Cui et al (2012), apparently the authors did not take into account the possibility that PCR products greater than 2000 bp would be difficult to sequence because the concentration of DNA that would be analy�ed would normally be too low (Pareek et al, 2011). Generally, 24 overlapping fragments using sets of he light-strand and heavy-strand oligonucleotide primers are needed to amplify the mitochondrial genome (Rieder et al, 1998).…”
mentioning
confidence: 99%
“…Dear Editor, In a recent report, Cui et al (2012) analy�ed the complete sequences of the mitochon-(2012) analy�ed the complete sequences of the mitochondrial genome of patients with aplastic anemia (AA). They concluded that (mtDNA) mutations are more frequent in patients with AA.…”
mentioning
confidence: 99%
See 1 more Smart Citation